The widowed women of Super Typhoon Haiyan a study on adaptation - Docena, Angelica M.; Lacaba, Shameem Marie G.; Turalba, Jessa C.; Brazas-Lim, Ladylyn (2016)
Super Typhoon Haiyan, or locally known as "Bagyong Yolanda" to the Filipinos, the victims had experienced social loss wherein individuals had experienced being detached from their roots either having their homes destroyed or the community that they once belonged to. The Super Typhoon Haiyan increased the number of widows due to its devastating effect on the Philippine archipelago.
This paper is anchored on Lazarus' theory of coping which states that coping is the sum of cognitive and behavioral efforts, which are constantly changing, and aims to handle particular demands, whether internal or external, that are viewed as taxing or demanding. Simply put, coping is an activity we do to seek and apply solutions to stressful situations or problems that emerge because of our stressors. In a disaster context, WHO defined coping as a capacity to respond and to recover from something stressful. Thus using the case study method, this paper looked into the different factors affecting the coping mechanism of widows, and validating whether remarrying is the best form of coping mechanism.
The results showed that remarrying is one of the coping mechanism of the widows but not the best. Findings also indicated emotional factor or the existence of their social support system as the factor that greatly affects the decision of the widows. Emotional factors are connected to psychological factor which was also found in the research. Next comes the economic factor. Findings also showed additional factors affecting the decision of the widows as to remarry or not. These factors are age, marital quality and circumstance of death of the spouse. Comparatively, findings showed a minimal difference between the present situation of those who remarried from those who did not. Furthermore, institutions affected the coping mechanism of women in terms of debriefing and forming of projects directed to women. The women, too, affected the role of the institutions through their current situation which becomes the sole basis for the forming of the projects of these institutions.
Undergraduate thesis (B.A.S.S. Political Science ) -- University of the Philippines, Tacloban.
Keywords: Social Sciences